O impacto da desoneração do ICMS nas exportações sobre a arrecadação do ICMS no estado do Ceará - Albuquerque, Gustavo Augusto Nunes de (2009)
The exemption of the Tax Movement of Goods and Services (ICMS) on exports of primary products and semi-manufactured products introduced by Complementary Law no. 87/96, known as the Kandir Law, aimed to increase the competitiveness of Brazilian exports and therefore increase the level of growth in the gross domestic product of Brazil. For the justification of the law, the expected economic effect from the tax relief was to generate positive internal revenue tax that would compensate (or more than offset) the losses of tax revenue suffered by the state of Ceará. This study aims to quantify and analyze the loss of tax revenue incurred by the state of Ceará for the period of 1991 to 2007, assuring that the Insurance Revenue Fund, the Budget and Financial Aid were enough to satisfactorily compensate the decrease in revenue. The literature on the subject, using different methodologies, shows many differences in the levels of losses in each State and that compensation arising from the federal government has not been sufficient to offset it. This paper uses the descriptive analysis of the data and analysis of the econometric model. It was found that there was a trend in exports, especially in manufacturing, revealing that the Kandir Law did not impact the expected size. The revenue collection, however, was affected by the tariff reduction, with implications of loss to the Treasury, which were not offset by the constitutional transfers. It can be concluded that the Kandir Law had a negative impact on the collection of ICMS, not identifying a new dynamic in the exports of Ceará.